2015
DOI: 10.1080/02791072.2015.1049725
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Sexual Debut and Initiation into New-Type Drug Use among a Sample of Young Adults

Abstract: We examined the association between adolescent sexual debut and age at new-type drug initiation among a sample of young adult new-type drug users. A total of 276 participants were recruited using respondent-driven sampling (RDS) in Shanghai, China. The analyses were restricted to a total of 201 participants aged between 18 and 30 years. The average age at sexual debut and age at first new-type drug use were 18.8 and 20.9 years, respectively. About 94% of participants reported having sexual experience (n = 188)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, adding it to the multivariable logistic model only led to modest changes in the aOR of the early sexual initiation on risky sexual practice. Given that repetitive preceding-sex use of illicit drugs presumably occurs following sexual initiation and empirical evidence suggests that the majority of Asian club drug users began their first club drug use after their sexual initiation [ 6 ], this pattern of attenuated aOR of the exposure after the adding of preceding-sex use of illicit drugs is compatible with its role as a mediator. Nevertheless, a mediator cannot be distinguished from a confounder solely based on the statistical change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, adding it to the multivariable logistic model only led to modest changes in the aOR of the early sexual initiation on risky sexual practice. Given that repetitive preceding-sex use of illicit drugs presumably occurs following sexual initiation and empirical evidence suggests that the majority of Asian club drug users began their first club drug use after their sexual initiation [ 6 ], this pattern of attenuated aOR of the exposure after the adding of preceding-sex use of illicit drugs is compatible with its role as a mediator. Nevertheless, a mediator cannot be distinguished from a confounder solely based on the statistical change.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from cross-country studies showed that substance use (measured by tobacco use frequency, alcohol use frequency, and ever drunk) was consistently associated with increased odds of early sexual initiation [ 1 , 34 ]. Earlier data in the US have pointed out that early-onset of marijuana or other illicit drugs were stronger predictors for having intercourse initiation before age 16 [ 35 ], although a study in East Asia indicated that the majority of club-drug users had sexual initiation before their first club-drug use [ 6 ]. The association of early initiation of illicit drug use with early initiation of sexual behavior might be attributed to shared underlying pathways, such as certain personality traits or disadvantaged environment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So these drugs were not being well controlled by relevant drug legislation [12]. There was an increase in the use of recreational drugs in China [11,13,14]. Using recreational drugs helped MSM deal with shame and vulnerability issues they might have from outside.…”
Section: Introductionmentioning
confidence: 99%